The Relationship Between Mother’s Nutritional Knowledge Towards Fruits Vegetables Consumption and Nutritional Status of Pre School Children Kindergarten Salman Jakarta - Mardhiah, D; Ekayanti, I; Setiawan, B (KnE Life Sciences, 2019)
Currently, obesity is an unsolved problem. Children obesity caused by high intake calorie and lack consumption of various food, especially fiber that extracted from fruits and vegetables. Mother’s knowledge about nutrition is essential, which influence level consumption of fruits and vegetables. The purpose of this research is to figure out the relationship between the mother’s nutritional knowledge towards fruits vegetable consumption and the nutritional status of preschool children of kindergarten Salman Jakarta. This research used a cross-sectional study design method. The sample consisted of 43 children, 4-6 years of age, selected based on a proportional random sampling. Mother’s nutritional knowledge and attitude measured by questionnaire. Fruits and vegetable consumption habits measured by food record for seven days and the Food Frequency Questionnaire (FFQ). Nutritional status of preschool children measured by using anthropometric method (IMT/U). The data analyzed by using descriptive statistics and Spearman correlation. The result shows that in general, the nutritional knowledge of mothers was in the moderate level of 53.5%. Most respondents had a positive attitude towards nutrition. Consumption of fruits and vegetable children was less than the serving size. The type of fruits that children often consumed was orange, banana, and papaya. The most vegetables are carrot, tomato, and spinach. The frequency is 7-14 times a week. Index rated by IMT/U shows that 18.6% of children had obesity nutritional status. Thus, the result of Spearman correlation proved there was no significant relationship between mother’s nutritional knowledge towards fruits vegetables consumption and nutritional status of preschool children (p>0,05). Keywords: nutritional knowledge, fruits, and vegetables, nutritional status